Antrodia cinnamomea Exhibits a Potent Neuroprotective Effect in the PC12 Cell-Aβ25–35 Model – Pharmacologically through Adenosine Receptors and Mitochondrial Pathway - Chang, Chi-Huang; Wang, Hui-Er; Liaw, Pei-Yu; Peng, Chiung-Chi; Peng, Robert Y. (Planta Medica, 2012)
Antrodia cinnamomea has a diversity of therapeutic effects including anticancer properties. Its neuroprotective effect is rarely cited. We hypothesized that due to its high phenol, triterpenoid, and adenosine contents, it might exhibit a potent neuroprotective effect. The PC12 cell model was used to investigate its pharmaceutical effects. Congo red staining was used to identify the activation of Aβ25–35. Chemical analysis indicated that the ethanolic extract of Antrodia cinnamomea contained a huge amount (mg/g ethanolic extract of Antrodia cinnamomea) of polyphenolics (133 ± 7), flavonoids (114 ± 6), triterpenoids (175 ± 26), and adenosine (370 ± 17). When tested with Aβ25–35 (15 µM), the cell viability was suppressed in a dose-dependent fashion with an IC50 value of 10 µM. The biochemical parameters upregulated by Aβ25–35 (15 µM) involved TNF-α, ROS, MDA, NO, and the intracellular calcium ions. These adverse effects were effectively ameliorated by the ethanolic extract of Antrodia cinnamomea (1 µg/mL). The Western blot analysis revealed that Aβ25–35 downregulated BcL-2/Bax and upregulated cleaved caspases-9 and − 3 without affecting cleaved caspase-8. The G2/M arrest elicited by Aβ25–35 was ameliorated by the ethanolic extract of Antrodia cinnamomea. TUNEL assay confirmed the apoptosis, and the ethanolic extract of Antrodia cinnamomea downregulated adenosine A1 and adenosine A2A receptors. Taken together, Aβ25–35 tends to induce neurotoxicity on PC12 cells. The ethanolic extract of Antrodia cinnamomea is capable of suppressing its neurotoxicity by rescuing the mitochondrial apoptosis pathway and simultaneously by downregulating adenosine A1 and adenosine A2A receptors to retard neurodegeneration and memory dysfunction.
Keywords: Antrodia cinnamomea; Fomitopsidaceae; apoptosis; adenosine receptor; neuroprotective; Aβ25–35